LEXIKON. Eintrag (Einzelartikel) - Ptashnyk, Stefaniya (WSK Grammatik (online-Publikation))

Bild/Bilderverbot (literaturwissenschaftlich) - Öhlschläger, Claudia (Lexikon der Bibelhermeneutik. Begriffe-Methoden. Theorien-Konzepte. Redaktion Susanne Luther)

Ikonographie (literaturwissenschaftlich) - Öhlschläger, Claudia (Lexikon der Bibelhermeneutik. Begriffe-Methoden. Theorien-Konzepte. Redaktion Susanne Luther)

Die Selbstverortung des Individuums zwischen Spätaufklärung und Romantik - Steigerwald, Jörn (Räume des Subjekts um 1800)

Ethik-Text-Kultur

Beeinflussung des Risswachstums durch Kerben in additiv gefertigten Strukturen - Reschetnik, W.; Brüggemann, J.P.; Kullmer, G.; Risse, L. (Additive Fertigung von Bauteilen und Strukturen – Neue Erkenntnisse und Praxisbeispiele)

Optimierung der Werkstoffperformance lasergeschmolzener metallischer Werkstoffe - Riemer, A.; Leuders, S.; Richard, H.A.; Kullmer, G.

A comparison of two variations of a pebble game on graphs - Meyer auf der Heide, Friedhelm (Automata, Languages and Programming. ICALP 1979)

Untere Zeitschranken für das Rucksack-Problem - Klein, P.; Meyer auf der Heide, Friedhelm (GI - 10. Jahrestagung)

Inseln im Ich

Handling Errors and Exceptions in the Algebraic Specifications of Data Types - Engels, Gregor; Pletat, Udo; Ehrich, Hans-Dietrich

Operational Semantics of Algebraic Specifications with Conditional Equations - Pletat, Udo; Engels, Gregor; Ehrich, Hans-Dietrich

Random access machines and straight-line programs - Meyer auf der Heide, Friedhelm; Rollik, Anton (Fundamentals of Computation Theory)

Time-processor trade-offs for universal parallel computers - Meyer auf der Heide, Friedhelm (Lecture Notes in Computer Science)

A comparison of two variations of a pebble game on graphs - Meyer auf der Heide, Friedhelm (Theoretical Computer Science)

Ein Kreiskriterium für Mehrgrößensysteme und seine Anwendung auf mechanische Schwingungssysteme - Böcker, Joachim

Specification of a Programming Support Environment by Graph Grammars - Engels, Gregor; Schäfer, Wilhelm (Proceedings of the conference on Graphtheoretic Concepts in Computer Science (WG`82), München (Germany))

An Operational Approach to Conditional Algebraic Specifications - Pletat, Udo; Engels, Gregor; Ehrich, Hans-Dietrich (Proceedings of the 7eme Colloque sur les Arbres en Algebre et en Programmation, Lille (France))
We suppose to give conditional specifications of abstract data types hierarchically. Considering algebraic specifications from an operational point of view this approach enables us to present simple syntactic criteria for the Church-Rosser property, which implies the welldefinedness of the operational semantics of a conditional specification. Furthermore, these criteria are su?cient for the termination of the full substitution reduction strategy.

Untersuchungen zur L_inf-Stabilität für eine Klasse nichtlinearer Regelungssysteme - Böcker, Joachim

Software Specification by Graph Grammars - Nagl, Manfred; Engels, Gregor; Gall, Rupert; Schäfer, Wilhelm (Proceedings of the 2nd International Workshop on Graph-Grammars and Their Application to Computer Science, Osnabrück (Germany))
The following paper demonstrates that programmed sequential graph grammars can be used in a systematic proceeding to specify the changes of high level intermediate data structures arising in a programming support environment, in which all tools work in an incremental and syntax-driven mode. In this paper we lay stress upon the way to get the specification rather than on the result of this process. Therefore, we give here some approach to specification engineering using graph grammars. This approach is influenced by the syntactical definition of the underlying programming language or module concept etc. to be supported but also by the idea of the user interface.

Software Specification Using Graph Grammars - Engels, Gregor; Gall, Rupert; Nagl, Manfred; Schäfer, Wilhelm (Computing)
The following paper,demonstrates that programmed sequential graph grammars can be used in a systematic proceeding to specify tbe changes of high level intermediate data structures arising in a programming support environment, in which all tools work in an incremental and syntax-driven mode. In this paper we lay stress upon the way to get the specification rather than on the result of this process. Therefore, we give here some approach to "specification engineering" using graph grammars. This approach is influenced by the syntactical definition of the underlying language for Programming in the Small, the module concept etc. to be supported on one side but also by the idea of the user interface.

An Operational Semantics for Specifications of Abstract Data Types with Error Handling - Engels, Gregor; Pletat, Udo; Ehrich, Hans-Dietrich (Acta Informatica)
A new approach to an operational treatment of errors and exceptions in specifications of abstract data types is presented. Considering a specification as a term rewriting system, we define an operational semantics and give conditions that are sufficient for its well-definedness (Church-Rosser property). Also, we give conditions that are sufficient for the termination of reduction strategies, respecting the specified error and exception handling.

Efficiency of universal parallel computers - Meyer auf der Heide, Friedhelm (Acta Informatica)

A lower time bound for the knapsack problem on random access machines - Klein, Peter; Meyer auf der Heide, Friedhelm (Acta Informatica)

Infinite cube-connected cycles - Meyer auf der Heide, Friedhelm (Information Processing Letters)

A polynomial linear search algorithm for the n-dimensional knapsack problem - Meyer auf der Heide, Friedhelm (Proceedings of the fifteenth annual ACM symposium on Theory of computing - STOC '83)

Efficiency of universal parallel computers - Meyer auf der Heide, Friedhelm (Lecture Notes in Computer Science)

Radar Image Simulation and its Application in Image Analysis - Domik, Gitta; Leberl, F.; Kobrick, M. (International archives of photogrammetry and remote sensing)

Rectification of Radar Images Using Stereo- Derived Height Models and Simulations - Domik, Gitta; Leberl, F.; Raggam, J. (XVth Congress of the International Society for Photogrammetry and Remote Sensing)

Evaluation of radar stereo viewability by means of a simulation technique - Domik, Gitta (ESA IGARSS 84: Remote Sensing: From Res. towards Operational Use,)

A Polynomial Linear Search Algorithm forr the n-Dimensional Knapsack Problem - Meyer auf der Heide, Friedhelm (Journal of the ACM (JACM))

On The Limits To Speed Up Parallel Machines By Large Hardware And Unbounded Communication - Meyer auf der Heide, Friedhelm; Reischuk, R. (25th Annual Symposium onFoundations of Computer Science, 1984.)

Efficient simulations among several models of parallel computers (extended abstract) - Meyer auf der Heide, Friedhelm (STACS 84)

Method to Relate Digital SAR Images and Map Information in Mountainous Areas - Domik, Gitta; Kienegger, E. (Proceedings of the World Conference on Remote Sensing)

The SAR-580 experiment on snow and glaciers at the Austrian test site - Rott, H.; Domik, Gitta (Proc. SAR-580 Investigators Workshop)

Differential Rectification of SLR-Images Using Map-Derived and Radar-Generated Digital Elevation Models. - Domik, Gitta; Leberl, Franz; Raggam, Johannes

Analyse von Radarbildern mittels digitaler Hoehenmodelle - Domik, Gitta; Kobrick, M; Leberl, Franz (Bildmessung und luftbildwesen)

Der nationalsozialistische „neue Begriff“ von Wissenschaft am Beispiel der „Deutschen Mathematik“ — Programm, Konzeption und politische Realisierung, Magisterarbeit an der Philosophischen Fakultät der Rheinisch-Westfälischen Technischen Hochschule Aachen, August 1984 - Peckhaus, Volker
Online-Version (2001, 2014): http://publications.rwth-aachen.de/record/229987

Das Schöne Als Vollzug Der Liebe. Eros-Logos-Verhältnisse in Platons Symposion - Hagengruber, Ruth Edith

Lie Theory of Semigroups - Hilgert, Joachim; Hofmann, K.H. (Semigroup Forum)

Radar image simulation as a tool to analyze topographic effects on geometry and radiometry of radar imagery - Domik, Gitta (Machine processing of remotely sensed data- Quantifying global process: Models, sensor systems, and analytical methods)

Radargrammetric aspects of SAR data evaluation - Raggam, J; Triebnig, Gerhard; Buchroithner, MF; Domik, Gitta; Leberl, Franz (Thematic Applications of SAR data)

Graph Grammar Engineering: A Method Used for the Development of an Integrated Programming Support Environment - Engels, Gregor; Schäfer, Wilhelm (Proceedings of the International Joint Conference on Theory and Practice of Software Development (TAPSOFT 1985), Berlin (Germany))
We introduce a method to specify the functional behaviour of software tools in an incremental and integrated software development environment. This specification method is based on graph grammars. It is an adequate method to specify the behaviour of all software systems using graphs as internal data structures. We show that a specification can be developed systematically by which the adaptability of the environment is increased towards modification of tools or extension by new tools. Furthermore, guidelines for the implementation can directly be derived from this specification.

The Design of an Adaptive and Portable Programming Support Environment - Engels, Gregor; Schäfer, Wilhelm (Proceedings of the International Computing Symposium, Amsterdam (The Netherlands))

Lower time bounds for integer programming with two variables - Lautemann, Clemens; Meyer auf der Heide, Friedhelm (Information Processing Letters)

Lower bounds for solving linear diophantine equations on random access machines - Meyer auf der Heide, Friedhelm (Journal of the ACM (JACM))

Simulating probabilistic by deterministic algebraic computation trees - Meyer auf der Heide, Friedhelm (Theoretical Computer Science)

The complexity of parallel sorting - Meyer auf der Heide, Friedhelm; Wigderson, Avi (26th Annual Symposium on Foundations of Computer Science (sfcs 1985))

One, two, three . . . infinity: lower bounds for parallel computation - Fich, F E; Meyer auf der Heide, Friedhelm; Ragde, P; Wigderson, A (Proceedings of the seventeenth annual ACM symposium on Theory of computing - STOC '85)

Fast algorithms for n-dimensional restrictions of hard problems - Meyer auf der Heide, Friedhelm (Proceedings of the seventeenth annual ACM symposium on Theory of computing - STOC '85)

Nondeterministic versus probabilistic linear search algorithms - Meyer auf der Heide, Friedhelm (26th Annual Symposium on Foundations of Computer Science (sfcs 1985))

Lower time bounds for solving linear diophantine equations on several parallel computational models - Meyer auf der Heide, Friedhelm (Information and Control)

Mapping with aircraft and satellite radar images - Leberl, FW; Kobrick, M; Domik, Gitta (The Photogrammetric Record)

Towards a SAR system for snow and land ice applications - Rott, H; Domik, Gitta; Mätzler, C; Miller, H (ESA Proceedings of a Workshop on Thematic Applications of SAR DATA p 29-39(SEE N 86-28488 19-42))

Distribution of Correlation Times in Glassy Polymers From Pulsed Deuteron NMR - Schmidt, Claudia; Kuhn, Karl J.; Spiess, Hans W. (Progress in Colloid and Polymer Science)

ELECTROOPTICAL BEHAVIOR OF CHOLESTERIC BLUE PHASES WITH NEGATIVE DIELECTRIC ANISOTROPY - HEPPKE, G; Kitzerow, Heinz-Siegfried; KRUMREY, M (MOLECULAR CRYSTALS AND LIQUID CRYSTALS)

ELECTRIC-FIELD INDUCED VARIATION OF THE REFRACTIVE-INDEX IN CHOLESTERIC BLUE PHASES - HEPPKE, G; Kitzerow, Heinz-Siegfried; KRUMREY, M (MOLECULAR CRYSTALS AND LIQUID CRYSTALS)

Controllabilty of Systems on Nilpotent Lie Groups - Hilgert, Joachim; Hofmann, K.H.; Lawson, J.D. (Beiträge Alg. Geom.)

Semigroups in Lie Groups, Semialgebras in Lie Algebras - Hilgert, Joachim; Hofmann, K.H. (Trans. AMS)

Lorentzian Cones in Real Lie Algebras - Hilgert, Joachim; Hofmann, K.H. (Monatshefte Math.)

Lie Semialgebras are Real Phenomena - Hilgert, Joachim; Hofmann, K.H. (Math. Ann.)

Old and New on SL(2) - Hilgert, Joachim; Hofmann, K.H. (Manuscripta Math.)

Architekten- und Künstlerbiographien - Seng, Eva- Maria (Ehrwürdige Zeugen verschwundener Tage, Tübinger Baudenkmale in Architekturzeichnungen des 19. Jahrhunderts, Katalog zur Ausstellung Tübingen 1986 (Tübinger Kataloge Nr. 29))

Classes of first order formulas under various satisfiability definitions - Kleine Büning, H.; Lettmann, Theodor (8th International Conference on Automated Deduction)

Die Zeichner und die Art der Darstellung - Zur Entwicklung und Funktion der Architekturzeichnung im 19. Jahrhundert - Seng, Eva- Maria (Ehrwürdige Zeugen verschwundener Tage, Tübinger Baudenkmale in Architekturzeichnungen des 19. Jahrhunderts, Katalog zur Ausstellung Tübingen 1986 (Tübinger Kataloge Nr. 29))

Das Ulmer Hauptwerk: Der Blaubeurer Hochaltar und die Erhart-Frage - Seng, Eva- Maria (Blätter für württembergische Kirchengeschichte, 86. Jg.)

Risse: Pytheas, Philostratos et. al. Zu den Protagonisten der frühen Erzählungen Arno Schmidts - Eke, Norbert Otto (Arno Schmidt. Das Frühwerk I: Erzählungen. Interpretationen von ‚Gadir‘ bis ‚Kosmas‘)

Belgium in a Nutshell Investitionsmöglichkeiten ausländischer Unternehmen in Belgien - Krimphove, Dieter

Multiple incidence angle SIR-B experiment over Argentina: generation of secondary image products - Domik, Gitta; Leberl, Franz; Cimino, Jobea (IEEE Transactions on Geoscience and Remote Sensing)

Digital terrain mapping with STAR-1 SAR data - Mercer, JB; Lowry, RT; Leberl, Franz; Domik, Gitta (International Geoscience and Remote Sensing Symposium)

Developing tools for digital radar image data evaluation - Domik, Gitta; Leberl, Franz; Raggam, J (Remote sensing for resources development and environmental management; Proceedings of the Seventh International Symposium)

On the Structure of an Incremental and Integrated Software Development Environment - Engels, Gregor; Lewerentz, Claus; Nagl, Manfred; Schäfer, Wilhelm (Proceedings of the 19th Hawaii International Conference on System Sciences, Hawaii, USA)

Experiences with a Hybrid-Interpreter Based on Incremental Compilation Techniques - Engels, Gregor; Sandbrink, Andrea (Proceedings of the Workshop on Compiler Compilers and Incremental Compilation Techniques, Bautzen)

Graphen als zentrale Datenstrukturen in einer Software-Entwicklungsumgebung - Engels, Gregor

Efficient Simulations among Several Models of Parallel Computers - Meyer auf der Heide, Friedhelm (SIAM Journal on Computing)

A tradeoff between search and update time for the implicit dictionary problem - Borodin, Allan; Fich, Faith E.; Meyer auf der Heide, Friedhelm; Upfal, Eli; Wigderson, Avi (Automata, Languages and Programming)

Speeding up random access machines by few processors - Meyer auf der Heide, Friedhelm (STACS 86)

A time-space tradeoff for element distinctness - Borodin, A.; Fich, F.; Meyer auf der Heide, Friedhelm; Upfal, E.; Wigderson, A. (STACS 86)

Radar Stereomapping Techniques and Application to SIR-B Images of Mt. Shasta - Leberl, F.; Domik, Gitta; Raggam, J.; Kobrick, M. (IEEE Transactions on Geoscience and Remote Sensing)

Multiple Incidence Angle SIR-B Expenment Over Argentina: Stereo-Radargrammetrc Analysis - Leberl, F.; Domik, Gitta; Raggam, J.; Cimino, J.; Kobrick, M. (IEEE Transactions on Geoscience and Remote Sensing)

An all digital implementation of a receiver for bandwidth-efficient communication - Oerder, Martin; Ascheid, Gerd; Haeb-Umbach, Reinhold; Meyr, Heinrich (Signal Processing: Theories and Applications)

Deformation dicker Punkte und Netze von Quadriken - Hellebrand, Sybille

Using secondary image products to aid in understanding and interpretation of radar imagery - Domik, Gitta; Leberl, Franz (IGARSS'86: Remote Sensing: Today's Solutions for Tomorrow's Information Needs)

Radargrammetric Experiments with Space Shuttle SIR-B Imagery - Leberl, Franz; Domik, Gitta; Raggam, J; Cimino, J; Kobrick, M (International archives of photogrammetry and remote sensing= Archives internationales de photogrammétrie et de télédétection= Internationales Archiv der Photogrammetrie und Fernerkundung)

Case Studies Towards the Establishment of a Social History of Logic - Peckhaus, Volker (History and Philosophy of Logic)
Abstracts: Historia Mathematica 18 (1991), 400 (#18.4.67); Historical Abstracts 39A:4291.

Nichtlineare und adaptive Regelungssysteme - Böcker, Joachim; Hartmann, Irmfried; Zwanzig, Christian

Dynamics of molecular reorientations: direct determination of rotational angles from two-dimensional NMR of powders - Schmidt, Claudia; Wefing, S.; Blümich, B.; Spiess, H.W. (Chemical Physics Letters)
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Eine empirische Untersuchung zu den schriftsprachlichen Leistungen türkischer Schulkinder - Beckemeyer, Rita; Tophinke, Doris (Narrative Kompetenz. Mündliche und schriftliche Wiedergabe von Erzählstrukturen durch türkische Schulkinder in außerschulischen Lerngruppen)

Geschlechtsspezifische Arbeitsteilung und technische Innovation - Neue Technologien, Frauenerwerbsarbeit und historisch-genetisches Lernen über Arbeit und Technik. - Bigga, Regine; Oberliesen, R. (Neue Technologien und technisch-ökonomische Bildung.)

ENDLESS POLARIZATION CONTROL EXPERIMENT WITH 3 ELEMENTS OF LIMITED BIREFRINGENCE RANGE - Noé, Reinhold (ELECTRONICS LETTERS)

ENDLESS POLARIZATION CONTROL IN COHERENT OPTICAL COMMUNICATIONS - Noé, Reinhold (ELECTRONICS LETTERS)

Optisches System mit einer Flüssigkristallzelle, Verfahren zu seinem Betrieb und seine Verwendung - Heppke, G.; Oestreicher, F.; Kitzerow, Heinz-Siegfried; Krumrey, M.

Das Städtische Orchester 1921–1955 - Grotjahn, Rebecca (Das Niedersächsische Staatsorchester 1636–1986)

Invariant Cones in Real Lie Algebras - Hilgert, Joachim; Hofmann, K.H. (Aspects of Positivity in Functional Analysis)

The Mayer-Vietoris and the Puppe Sequence in K-Theory for C*-algebras - Hilgert, Joachim (Studia Math.)

On the Automorphism Group of Cones and Wedges - Hilgert, Joachim; Hofmann, K.H. (Geom. Dedicata)

On Sophus Lie's Fundamental Theorem - Hilgert, Joachim; Hofmann, K.H. (J. Funct. Anal.)

Representation independent query and update operations on propositional definite Horn formulas - Büning, Hans Kleine; Lettmann, Theodor (Computation Theory and Logic)

DFG fördert an der FAU: Projekt: Fallstudien zur Begründung einer Sozialgeschichte der Logik - Peckhaus, Volker; Thiel, Christian (FAU Uni-Kurier)

Ein Hauch von Paris ... Die Planung für den Tübinger Uhlandplatz durch Christian Friedrich von Leins - Seng, Eva- Maria (Tübinger Blätter, 74. Jg.)

Image based SAR product simulation for analysis - Domik, Gitta; Leberl, Franz (ASPRS-ACSM)

A Hybrid Interpreter in a Software Development Environment - Engels, Gregor; Schürr, Andy (Proceedings of the 1st European Software Engineering Conference (ESEC '87), Strasbourg (France))
This paper describes the realization of an execution tool for Modula-2 modules which is part of an integrated tool set in a software development environment termed IPSEN (Incremental Programming Support Environment). In this environment, all software documents, e.g. Modula-2 modules, are manipulated by syntax-directed editors and are represented internally by attributed graphs. The execution of Modula-2 modules is done by two cooperating interpreters. The first one is a graph interpreter which traverses the internal graph from statement to statement. These statements are translated into a low-level, more efficiently executable object code and interpreted by a second interpreter. This concept of a hybrid interpreter allows the realization of an execution tool which offers a lot of runtime support features to the user.

On the Structure of Structure-Oriented Editors for Different Applications - Engels, Gregor; Nagl, Manfred; Schäfer, Wilhelm (Proceedings of the ACM SIGSOFT/SIGPLAN Software Engineering Symposium on Practical Software Development Environments, Palo Alto, USA)

Graph Grammar Engineering: A Software Specification Method - Engels, Gregor; Lewerentz, Claus; Schäfer, Wilhelm (Proceedings of the 3rd International Workshop on Graph-Grammars and Their Application to Computer Science, Warrenton, VA (USA))
Graphs as conceptual data models are accepted and used in a wide range of different problem areas. Giving some examples we outline common aspects for modeling complex structures by graphs. We present a formal frame-work based on graph grammars to specify graph classes and the corresponding graph manipulations. We show that such a specification can be written in a systematic, engineering-like manner. This is achieved by an extension of the known programmed, attributed graph grammars. Node-set operators are introduced to facilitate graph queries. Concepts like abstraction, decomposition, refinement, parameterization, and integration have been adopted from software engineering to yield a comprehensive specification method. This method has successfully been applied to specify the central data structures in a software development environment project

A Time-Space Tradeoff for Element Distinctness - Borodin, A.; Fich, F.; Meyer auf der Heide, Friedhelm; Upfal, E.; Wigderson, A. (SIAM Journal on Computing)

The Complexity of Parallel Sorting - Meyer auf der Heide, Friedhelm; Wigderson, Avi (SIAM Journal on Computing)

Digital Rectification Method for Radar Images Applied on Huge Arrays - Domik, Gitta (Proceedings of the First Int'l. Workshop on Image Rectification Tech. for Spaceborne Synthetic Aperture Radar)

Optimal Carrier Recovery and Detection on Frequency-Nonselective Fading Channels - Haeb-Umbach, Reinhold; Meyr, Heinrich (Proc. Symposium on Inf. Theory and Appl. (SITA), Tokio)

Methods and application of surface shape reconstruction from multiple SAR images - Domik, Gitta (IGARSS'87-International Geoscience and Remote Sensing Symposium)

Methods and accuracy of operational digital image mapping with aircraft SAR - Leberl, Franz; Domik, Gitta; Mercer, Bryan J (1987 ASPRS ACSM Annual Convention)

Interdisziplinäres Institut für Wissenschaftstheorie und Wissenschaftsgeschichte - Peckhaus, Volker; Kötter, Rudolf (Friedrich-Alexander-Universität Erlangen-Nürnberg. Jahresbericht 1984/85 und 1985/86 (Mai 1987))

Molecular motions from two-dimensional NMR of powders: Comparison of rotational jumps and diffusive reorientations - Schmidt, Claudia; Blümich, B.; Wefing, S.; Kaufmann, S.; Spiess, H. W. (Berichte der Bunsengesellschaft für physikalische Chemie)
Keywords: General Chemical Engineering

Anschauliches Lernen im Museum. - Bigga, Regine (Allgemeinbildung und Arbeit, Technik, Wirtschaft - Innovationen in Curriculum und Schul-Praxis.)

Ruth Crawford Seeger - Grotjahn, Rebecca (Amerikanische Musik seit Charles Ives)

Wallingford Riegger - Grotjahn, Rebecca (Amerikanische Musik seit Charles Ives)

George Rochberg - Grotjahn, Rebecca (Amerikanische Musik seit Charles Ives)

Angular Dependence of Blue Phase Selective Reflection in the Electric Field - Heppke, G.; Kitzerow, Heinz-Siegfried; Krumrey, M. (Molecular Crystals and Liquid Crystals Incorporating Nonlinear Optics)
Keywords: General Medicine

Theoretische und numerische Aspekte der Berechnung thermo-mechanischer Kriechvorgänge im Steinsalz - Mahnken, Rolf; Stein, Erwin; Wetjen, Diedrich; Heemann, Ulrich (Abhandlungen der Braunschweigischen Wissenschaftlichen Gesellschaft)

Maximal Semigroups and the Support of Gauss-Semigroups - Hilgert, Joachim (Probability and Baysian Statistics)

Maximal Semigroups and Controllability in Products of Lie Groups - Hilgert, Joachim (Archiv Math.)

Perspektiven für die Logikprogrammierung - Kleine Büning, Hans; Lettmann, Theodor (Workshop Wissensrepräsentation in Expertensystemen)

Historiographie wissenschaftlicher Disziplinen als Kombination von Problem- und Sozialgeschichtsschreibung: Formale Logik im Deutschland des ausgehenden 19. Jahrhunderts - Peckhaus, Volker (Die geschichtliche Perspektive in den Disziplinen der Wissenschaftsforschung. Kolloquium an der TU Berlin, Oktober 1988. Mit Beiträgen von Michael Heidelberger, Walter Kaiser, C. Ulises Moulines, Volker Peckhaus, Wolf Schäfer, Burghard Weiss)

Die Johanneskirche am Feuersee in Stuttgart und der Architekt Christian Friedrich von Leins (1814 - 1892), Magisterarbeit masch. - Seng, Eva- Maria

„Wenn man die Augen hätte schließen und schlafen können...“. Zu Arno Schmidts Nachkriegsroman „Brand’s Haide“ - Eke, Norbert Otto (Arno Schmidt. Das Frühwerk II. Romane. Interpretationen von ‚Brand’s Haide’ bis ‚Gelehrtenrepublik’)

A Highly Integrated Tool Set for Program Development Support - Engels, Gregor; Janning, Thorsten; Schäfer, Wilhelm (Proceedings of the conference on ACM SIGSMALL/PC symposium on ACTES (SIGSMALL 1988), Cannes (France))
This paper describes the design of the integrated user interface of the software development environment IPSEN (Integrated Programming Support Environment). We explain the characteristic features of the IPSEN user interface, namely the structured layout of the screen, the command-driven tool activation, and especially the highly integrated use of the IPSEN tool set. We demonstrate those features by taking a sample set of tools of the IPSEN environment. That tool set supports all the programming-in-the-small activities within IPSEN. Finally, we sketch the realization of two prototypes running on an IBM-AT and a net of SUN workstations.

Konzeption einer integrierten Datenbank-Entwurfsumgebung - Engels, Gregor; Hohenstein, Uwe; Neugebauer, Leonore; Saake, Gunter; Ehrich, Hans-Dietrich (Proceedings of DBTA/SI Data Dictionaries und Entwicklungswerkzeuge für Datenbank-Anwendungen, Zürich, Switzerland)

Auf dem Weg zu einer integrierten Datenbank-Entwurfsumgebung - Engels, Gregor; Hohenstein, Uwe; Saake, Gunter; Ehrich, Hans-Dietrich (Proceedings of the GI-Workshop on "Sprachspezifische Programmierumgebungen")

Ein Konzept zur Beschreibung von Software-Architekturen - Ebert, Jürgen; Engels, Gregor

Die Benutzerschnittstelle einer integrierten Modula-2 Programmentwicklungsumgebung - Engels, Gregor; Janning, Thorsten; Schäfer, Wilhelm (Proceedings of GI-Workshop Sprachspezifische Programmierumgebungen, Darmstadt, Germany)

On the limits of computations with the floor function - Babai, László; Just, Bettina; Meyer auf der Heide, Friedhelm (Information and Computation)

Fast algorithms for N-dimensional restrictions of hard problems - Meyer auf der Heide, Friedhelm (Journal of the ACM (JACM))

A tradeoff between search and update time for the implicit dictionary problem - Borodin, Allan; Fich, Faith E.; Meyer auf der Heide, Friedhelm; Upfal, Eli; Wigderson, Avi (Theoretical Computer Science)

Dynamic perfect hashing: upper and lower bounds - Dietzfelbinger, M.; Karlin, A.; Mehlhorn, K.; Meyer auf der Heide, Friedhelm; Rohnert, H.; Tarjan, R.E. ([Proceedings 1988] 29th Annual Symposium on Foundations of Computer Science)

On computations with integer division - Just, Bettina; Mathematik, Fb; Meyer auf der Heide, Friedhelm; Informatik, Fb; Wigderson, Avi (STACS 88)

Upper and lower bounds for the dictionary problem - Dietzfelbinger, M.; Mehlhorn, K.; Meyer auf der Heide, Friedhelm; Rohnert, H. (SWAT 88)

Enhancement Techniques in Digital Image Processing - Domik, Gitta (Proceedings of the Computer Science Symposium)

A Comparison of Coherent and Differentially Coherent Detection Schemes for Fading Channels - Haeb-Umbach, Reinhold (International Conference on Vehicular Technology, Philadelphia)
The common basis of coherent and differentially coherent detection is considered from the viewpoint of carrier recovery as the estimation of fading distortion. In the differentially coherent receiver a simple estimate of the fading distortion is used whereas the coherent receiver uses the optimal estimate. The bit error rates (BERs) for M-ary PSK (phase-shift keyed) and DPSK (double phase-shift keyed) transmission are calculated using a single method of calculation for both detection schemes. The calculation takes into account nonperfect carrier recovery, cochannel interference, and diversity. The results allow a direct comparison of the two schemes and show that coherent detection is preferable in many realistic fading environments.

A digital Synchronizer for Linearly Modulated Signals Transmitted over a Frequency-Nonselective Fading Channel - Haeb-Umbach, Reinhold; Meyr, Heinrich (International Conference on Communications, Philadelphia)
A digital carrier recovery structure which allows coherent detection on frequency-nonselective fading channels is presented. The synchronizer estimates the multiplicative distortion introduced by the channel. It is shown that the structure is superior to a phase-locked loop and is well suited for a fully digital realization. A detailed synchronizer design and simulation results are presented for a land-mobile radio channel. This includes a novel scheme for a fully digital frequency offset estimation and correction.

A multi-spectral analysis system using large databases. - Brugel, Edward W; Domik, Gitta; Voels, Stephen A (European Southern Observatory Conference and Workshop Proceedings)

Dependence of image grey values on topography in SIR-B images - Domik, Gitta; Leberl, Franz; Cimino, J (International Journal of Remote Sensing)

SIR-B stereo-radargrammetry of Australia - Leberl, Franz; Mayr, W; Domik, Gitta; Kobrick, M (International journal of remote sensing)

Karl Eugen Müller (1865–1932) und seine Rolle in der Entwicklung der Algebra der Logik - Peckhaus, Volker (History and Philosophy of Logic)
Abstracts: The Philosopher's Index. Cumulative Edition 22 (1988), 509–510; Historical Abstracts 40A:4245. Rezensionen: Zbl. Math. 645.01019 (R. Murawski); MR 89e:01038 (Chris Brink).

Modellierung der dissipativen Eigenschaften linearer passiver Systeme unter Verwendung der Distributionentheorie - Böcker, Joachim

Generating Pattern Sequences for the Pseudo-Exhaustive Test of MOS-Circuits - Wunderlich, Hans-Joachim; Hellebrand, Sybille (18th International Symposium on Fault-Tolerant Computing, FTCS-18)

Integrated Tools for Automatic Design for Testability - Schmid, Detlef; Wunderlich, Hans-Joachim; Feldbusch, Fridtjof; Hellebrand, Sybille; Holzinger, Juergen; Kunzmann, Arno (Tool Integration and Design Environments, F.J. Rammig (Editor))

Automatisierung des Entwurfs vollständig testbarer Schaltungen - Hellebrand, Sybille; Wunderlich, Hans-Joachim (GI - 18. Jahrestagung II, Hamburg, 1988, Informatik-Fachberichte 188)

Magnetic-field-induced orientation of crystallites in powders of layered intercalation compounds detected by NMR - Halstead, Thomas K.; Schmidt, Claudia; Spiess, Hans W.; Schoellhorn, Robert; Mueller-Warmuth, Werner; Moeller, H. (The Journal of Physical Chemistry)
Keywords: Physical and Theoretical Chemistry; General Engineering

Deuteron two-dimensional exchange NMR in solids - Schmidt, Claudia; Blümich, B; Spiess, H.W (Journal of Magnetic Resonance (1969))
Keywords: General Engineering

Studium Arbeitslehre - Rückblick mit Ausblick - Bigga, Regine (Arbeitslehre / Polytechnik: Ein Beitrag zur Neuen Allgemeinbildung. Die Geschichte von Arbeit, Technik und Produktion im Unterricht)

Die Schleswig-Holsteinische Volkszeitung 1892 bis 1968 - Facetten aus ihrer Geschichte - Bigga, Regine; Danker, Uwe (Beirat für Geschichte der Arbeiterbewegung und Demokratie in Schleswig-Holstein)

Der VZ - Verlag in Photographien - Bigga, Regine; Danker, Uwe; Bruhn, Paul (Beirat für Geschichte der Arbeiterbewegung und Demokratie in Schleswig-Holstein)

INTEGRATED-OPTIC ROTATING WAVEPLATE FREQUENCY SHIFTER - Noé, Reinhold; SMITH, DA (ELECTRONICS LETTERS)

NEW FSK PHASE-DIVERSITY RECEIVER IN A 150 MBIT/S COHERENT OPTICAL-TRANSMISSION SYSTEM - Noé, Reinhold; SESSA, WB; WELTER, R; KAZOVSKY, LG (ELECTRONICS LETTERS)

ENDLESS POLARIZATION CONTROL-SYSTEMS FOR COHERENT OPTICS - Noé, Reinhold; HEIDRICH, H; HOFFMANN, D (JOURNAL OF LIGHTWAVE TECHNOLOGY)

INTEGRATED-OPTIC ROTATING WAVEPLATE FREQUENCY SHIFTER - Noé, Reinhold; SMITH, DA (ELECTRONICS LETTERS)

NEW FSK PHASE-DIVERSITY RECEIVER IN A 150 MBIT/S COHERENT OPTICAL-TRANSMISSION SYSTEM - Noé, Reinhold; SESSA, WB; WELTER, R; KAZOVSKY, LG (ELECTRONICS LETTERS)

ENDLESS POLARIZATION CONTROL-SYSTEMS FOR COHERENT OPTICS - Noé, Reinhold; HEIDRICH, H; HOFFMANN, D (JOURNAL OF LIGHTWAVE TECHNOLOGY)

AUTOMATIC ENDLESS POLARIZATION CONTROL WITH INTEGRATED-OPTICAL TI-LINBO3 POLARIZATION TRANSFORMERS - Noé, Reinhold; HEIDRICH, H; HOFFMANN, D (OPTICS LETTERS)

Blue phase liquid crystal system, method of operation and its use - Kitzerow, Heinz-Siegfried; Heppke, G.; Oestreicher, F.; Kitzerow, Heinz-Siegfried; Krumrey, M.

Electrooptic Effect in a Non-Polar Nematic Discotic Liquid Crystal - Heppke, G.; Kitzerow, Heinz-Siegfried; Oestreicher, F.; Quentel, S.; Ranft, A. (Molecular Crystals and Liquid Crystals Letters)

Rez.: Andreas Feige / Ingrid Lukatis / Wolfgang Lukatis: Kirchentag zwischen Kirche und Welt. Auf der Suche nach Antworten. Eine empirische Untersuchung auf dem 21. Deutschen Evangelischen Kirchentag Düsseldorf 1985 - Schroeter-Wittke, Harald (Der Evangelische Erzieher)

Schätze in irdenen Gefäßen - sind unsere neueren Tauflieder verwässert und vergeistigt? - Schroeter-Wittke, Harald (Der Evangelische Erzieher)

Spectrally Ordered Lie Algebras - Hilgert, Joachim (Group Theoretical Methods in Physics)

Invariant Lorentzian Orders on Simply Connected Lie Groups - Hilgert, Joachim (Arkiv för mat.)

Classification of Invariant Cones in Real Lie Algebras - Hilgert, Joachim; Hofmann, K.H. (Bull. AMS)

Invariant Cones in Lie Algebras - Hilgert, Joachim; Hofmann, K.H. (Semigroup Forum 37l. Semigroup Forum)

Friedrich Halm - Eke, Norbert Otto (Literatur Lexikon. Autoren und Werke deutscher Sprache. Bd. 4)

Dieter Forte - Eke, Norbert Otto (Harenbergs Lexikon der Weltliteratur. Autoren – Werke – Begriffe. Bd. 2)

Herta Müller - Eke, Norbert Otto (Harenbergs Lexikon der Weltliteratur. Autoren – Werke – Begriffe. Bd. 4)

Norbert Mecklenburg: Erzählte Provinz. Regionalismus und Moderne im Roman. Königstein/Ts. 2. Auflage. 1986 - Eke, Norbert Otto (Germanistik. Internationales Referatenorgan mit bibliographischen Hinweisen)

Projections of vector addition system reachability sets are semilinear - Kleine Büning, Hans; Lettmann, Theodor; Mayr, Ernst W. (Theoretical Computer Science)

Erstellung einer Ton-Dia-Schau zum Einsatz im schulischen Unterricht für den Kreis Lippe zum 40. Jubiläum des Art. 3 Abs. 2 Grundgesetz “Männer und Frauen sind gleichberechtigt” - Schlegel-Matthies, Kirsten

Chaos in the Market of Foreign Exchange, in: Rieder, Gessner, Peyer, Immhoff, Radermacher (eds) - Gries, Thomas

Heiner Müller. Apokalypse und Utopie - Eke, Norbert Otto

Nikolaus Lenau. Werke und Briefe. Historisch-kritische Gesamtausgabe. Bd. 5,1: Briefe 1812-1837. Teil 1: Text (Edition) - Eke, Norbert Otto; Vizkelety, András; Skrodzki, Karl Jürgen; Steinecke, Hartmut

Vom Ballhaus zum Gotteshaus, Vorgeschichte und Bau der katholischen St. Johannes-Kirche in Tübingen - Seng, Eva- Maria (Tübinger Blätter, 76. Jg.)

Verfahren zur flankenspielorientierten Einstellung von Kegelrad- und Hypoidradsätzen - Langenbeck, Konrad; Zimmer, Detmar (VDI-Z - Zeitschrift des Vereins Deutscher Ingenieure für Maschinenbau und Metallbearbeitung)

Automatisierte Einstellung von Kegelrad- und Hypoidradsätzen - Langenbeck, Konrad; Zimmer, Detmar (antriebstechnik - Zeitschrift für Konstruktion, Entwicklung und Anwendung von Antrieben und Steuerungen)

Flankenspielorientierte Einstellung der Hypoid- und Kegelradgetriebe - Zimmer, Detmar

Konzepte einer Software-Architektur-Beschreibungssprache - Ebert, Jürgen; Engels, Gregor (Software-Entwicklung: Konzepte, Erfahrungen, Perspektiven, Fachtagung, 1989, Marburg (Germany))

CADDY-O: Syntaxgestütztes, graphisches Entwerfen konzeptioneller Datenbankschemata - Engels, Gregor (Tagungsband GI-Fachtagung "Interaktive Schnittstellen für Informationssysteme", TU Clausthal, Notizen zu Interaktive Systeme)

CADDY: Computer-Aided Design of Non-Standard Databases - Engels, Gregor; Hohenstein, Uwe; Hülsmann, Klaus; Löhr-Richter, Perdita; Ehrich, Hans-Dietrich (Proceedings of the International Conference on System Development Environments & Factories, Berlin, Germany)

Benutzerschnittstelle und Architektur der integrierten Datenbankentwurfsumgebung CADDY (Kurzfassung) - Engels, Gregor

Programmentwicklungsumgebungen: Konzepte und Realisierung - Engels, Gregor; Schäfer, Wilhelm

Computational methods for bifurcation problems with symmetries—with special attention to steady state and Hopf bifurcation points - Dellnitz, Michael; Werner, Bodo (Journal of Computational and Applied Mathematics)

On computations with integer division - Just, Bettina; Meyer auf der Heide, Friedhelm; Wigderson, Avi (RAIRO - Theoretical Informatics and Applications)

An optimal parallel dictionary - Dietzfelbinger, M.; Meyer auf der Heide, Friedhelm (Proceedings of the first annual ACM symposium on Parallel algorithms and architectures - SPAA '89)

On genuinely time bounded computations - Meyer auf der Heide, Friedhelm (STACS 89)

Time-optimal simulations of networks by universal parallel computers - Meyer auf der Heide, Friedhelm; Wanka, Rolf (STACS 89)

Computing minimum spanning forests on 1- and 2-dimensional processor arrays - Meyer auf der Heide, Friedhelm (STACS 89)

Geometry and Action-Angle Variables of Multi Soliton Systems - Fuchssteiner, Benno; Oevel, Gudrun (Rev. Math. Phys.)

A systematic approach to carrier recovery and detection of digitally phase modulated signals on fading channels - Haeb-Umbach, Reinhold; Meyr, Heinrich (IEEE Transactions on Communications)
The problem of optimal carrier recovery and detection of digitally phase modulated signals on fading channels by using a nonstructured approach is presented, i.e. no constraint is placed on the receiver structure. First, the optimal receiver is derived for digitally phase-modulated signals when transmitted over a frequency-nonselective fading channel with memory. The memory results from the fact that usually the coherence time of the channel is larger than the symbol period. Symbols adjacent in time cannot be detected independently and therefore the well-known quadratic receiver is not optimal in this case. A maximum a posteriori (MAP) detector is derived and explicitly utilizes the channel memory for carrier recovery. The derivation shows that the optimal carrier recovery is, under certain conditions, a Kalman filter. Some attractive properties of this carrier recovery unit (including the absence of hang up) are discussed. Then the error rate of several digital modulation schemes is calculated taking the performance of the filter into account. The differences in susceptibility of the modulation schemes to carrier phase jitter are specified.

Die Institutionalisierung der Mathematischen Logik in Deutschland - Peckhaus, Volker (XVIIIth International Congress of History of Science. General Theme: Science and Political Order. Wissenschaft und Staat. 1st — 9th August 1989 Hamburg — München. Abstracts)

The Pseudo-Exhaustive Test of Sequential Circuits - Wunderlich, Hans-Joachim; Hellebrand, Sybille (IEEE International Test Conference (ITC'89))

Plattdeutsch - ein Pflegefall?

PATTERN-INDEPENDENT FSK HETERODYNE TRANSMISSION WITH ENDLESS POLARIZATION CONTROL AND A 119 PHOTOELECTRONS BIT RECEIVER SENSITIVITY - Noé, Reinhold; RODLER, H; EBBERG, A; GAUKEL, G; AURACHER, F (FIBER AND INTEGRATED OPTICS)

POLARIZATION-INSENSITIVE, 500 MBIT/S FSK TRANSMISSION OVER 153KM BY PASSIVE POLARIZATION SWITCHING - Noé, Reinhold; GIMLETT, JL; VODHANEL, RS; TSUJI, S (ELECTRONICS LETTERS)

POLARIZATION-INSENSITIVE, 500 MBIT/S FSK TRANSMISSION OVER 153KM BY PASSIVE POLARIZATION SWITCHING - Noé, Reinhold; GIMLETT, JL; VODHANEL, RS; TSUJI, S (ELECTRONICS LETTERS)

ODICE: Object-Oriented Hardware Description in CAD Environment - Rammig, Franz Josef; Müller, Wolfgang (Proc. of the Ninth IFIP Symposium on CHDLs and their Application)

Observation of a hexagonal blue phase in systems with negative dielectric anisotropy - Heppke, G.; Jéròme, B.; Kitzerow, Heinz-Siegfried; Pieranski, P. (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry